The Concept of Justice in Compensation Arrangements to Realize the Establishment of National Law - Wahyu Prawesthi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Providing compensation is an effort to achieve justice for parties who experience losses in various legal contexts, including in data defense, criminal and administrative matters. The concept of justice in providing compensation in Indonesia needs to be understood as part of efforts to establish national law that reflects community values ​​and national interests. Justice is not only limited to providing rights to the injured party, but also includes providing balanced sanctions to the party who caused the loss. The existence of clear and consistent regulations regarding compensation will increase public confidence in the national legal system and prevent legal violations. The formation of national law based on the concept of justice in providing compensation also needs to take into account universal principles and relevant norms. This effort includes synchronizing regulations between legal sectors and strengthening the role of judicial institutions in providing fair compensation. Thus, it is hoped that regulations regarding fair compensation can support the formation of national laws that are responsive, progressive and fair for all Indonesian people